2011
DOI: 10.1039/c0cp01626h
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally promoted electron emission at a metal surface: electron kinetic energy distributions

Abstract: We report the first direct measurement of the kinetic energy of exoelectrons produced by collisions of vibrationally excited molecules with a low work function metal surface exhibiting electron excitations of 64% (most probable) and 95% (maximum) of the initial vibrational energy. This remarkable efficiency for vibrational-to-electronic energy transfer is in good agreement with previous results suggesting the coupling of multiple vibrational quanta to a single electron.Understanding the interactions of molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 24 publications
(43 reference statements)
2
30
0
Order By: Relevance
“…This study revealed very efficient multiquantum transfer of molecular vibration to the metal, in contrast to results for the same molecule scattered from an insulator, where vibration was transferred inefficiently 3b. 4 Similar experiments on low work function materials even showed vibrationally promoted exoelectron emission 3df…”
mentioning
confidence: 56%
“…This study revealed very efficient multiquantum transfer of molecular vibration to the metal, in contrast to results for the same molecule scattered from an insulator, where vibration was transferred inefficiently 3b. 4 Similar experiments on low work function materials even showed vibrationally promoted exoelectron emission 3df…”
mentioning
confidence: 56%
“…There is now considerable experimental evidence that vibrational excitation and de-excitation in NO collisions with Au and Ag surfaces are due to the nonadiabatic coupling to the electronhole pairs in the metal. [3][4][5][6]8,9,[29][30][31][32][33] In such a strongly electronically nonadiabatic system, translational motion was historically considered a spectator to the vibrational energy transfer. 12,14 While increased incidence energy of translation can increase the nonadiabatic coupling strength, it was thought to not directly exchange energy with the vibrational DOF.…”
Section: Vibration-to-translation Energy Transfermentioning
confidence: 99%
“…The ample evidence of energy exchange between molecular vibrations and metallic EHPs gained from molecular beam-surface scattering experiments includes studies of (single and multi-quantum) vibrational excitation, 8,9,12 (single and multi-quantum) vibrational relaxation, 4,28 and electron emission 5,6,29 occurring in the course of molecule-surface encounters. Specifically, vibrational excitation exhibiting an Arrhenius-like surface temperature dependence with activation energy equal to the vibrational excitation energy is often considered to be a signature a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%